FLORA ETNOMEDICINAL EMPLEADA POR EL POBLADOR DEL DISTRITO DE LA ESPERANZA, TRUJILLO, LA LIBERTAD, 2019 - BENITES RUIZ, Stefany Geraldine (2019)
Peru harbors an extraordinary Floristic wealth that man through its history took advantage of to meet his needs; ancestral ethnobotanical wisdom, taught initially by the "Hampicamayoc", "Oquetlupuc", "Sircac", and which, at present, persists through the "healers", " emollients " and "grandmothers"; but unfortunately it has been lost due to the lack of communication and registration. As described, the objective of this research was to determine the ethnomedicinal flora of the district of La Esperanza, Trujillo, La L ibertad. For this, 96 semi - structured interviews were applied to the buyers and sellers of medicinal plants ofthe most representative markets of the district in question; In parallel, collection, drying, assembly , and labeling of botanical specimens were carried out; then determine its taxonomic characteristics: family , scientific and common name; and ethnobotanicals: part used, form of preparation and medicinal uses. Was repo rtan 65 species of medicinal plants used in district l Esperanza, distributed in 35 f amilies and 61 genera, being the most representative families: Asteraceae (7 ), Lamiaceae (7) and Rutaceae (4); and the important species , catalogedby the resident of the district of Hope : Solanum tuberosum L. (IVU = 0.97), Allium sativum L. (IVU = 0.95), Linum usitatissimum L. (IVU = 0.95), Allium cepa L. (IVU = 0.94 ), Citrus Lemon (L.) Osbeck (IVU = 0.94), Hordeum vulgare L. (IVU = 0.92), Zea mays L. (IVU = 0.92), Citrus × aurantium L. (IVU = 0.92), Cucurbita pepo L. (IVU = 0.90), Aloe vera (L.) Burm.f . (IVU = 0.90), Ananas comosus (L.) Merr . (IVU = 0.86), Musa × paradisiaca L. (IVU = 0.86), Malus communis Lam. (IVU = 0.86), Citrus aurantiifolia ( Christm .) Swingle (IVU = 0.86).